Crop Protection and Its Effectiveness against Wildlife: A Case Study of Two Villages of Shivapuri National Park, Nepal - Pandey, Sudip; Bajracharya, Siddhartha Bajra (Nepal Journal of Science and Technology, 2016)
A complex relationship between the residents and protected areas continue to be an obstacle to successful conservation of protected areas. Conflicts between park authority and people living around the park pose a threat to conservation. Moreover, crop depredation due to wildlife incurs a severe economic loss to communities living in the close vicinity of the park, affecting the livelihood and well-being of locals. Many studies have been carried out emphasizing the identification and quantification of crop damage, but studies highlighting the means used for the crop protection and their effectiveness are limited. This paper examines frequency of the crop damage by wildlife and efficacy of utilized management practices in Shivapuri National Park (SNP). Altogether 132 households were visited in two buffer zone villages namely, Sikre and Jhor Mahankhal of Shivapuri National Park, Nepal. The study suggested that crop depredation by wildlife was a function of several factors, namely, distance of the farmland from the park, size of the crop raiding animals, frequency of their attacks on the farmland, and the type of crops. Five different measures were identified by the communities which they regularly used to prevent crop damage. Both traditional as well as modern means were used by households to guard crops from invading wild animals. The means of crop protection from wildlife differed according to the type of animal and crop being protected. Biofencing and trenches were effective for the small animals. Watch tower “Machans” and throwing flaming sticks and making noises were the most effective and safest means of crop guarding from all kind of animals. Though crop guarding was intensive, no means were found to be able to prevent crop damage completely. Thus, site specific management strategies as well as technical and financial support from donor organizations would be most useful to minimize crop loss. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 1-10